Improving Students’ Writing Skill in Recount Text by Using Picture Series Medium - Lyza Yustika (Juliet, 2021)
This research aimed to describe how picture series medium can increase the students’s writing skill for eighth grade at state junior high school 1 of Bintan. Classroom action research was the research design. The research comprised of two cycles with four meeting in the two cycles. A test was the main data of this research. Twenty students in VIII B at state junior high school 1 of Bintan, in the academic year of 019/2020 was the subject of this research. The outcome appeared there were upgrades in students’ writing skill. It tends to be seen from the outcome of each post-test in the two cycles. Students’ test average in cycle 1 was 63.57. Students’ test average in second cycle was 68.87. It means picture series medium could help students in improving their writing skill.